Analisis kebutuhan pengembangan lembar kerja mahasiswa berbasis model pembelajaran IDEA - Yayan Eryk Setiawan; Ahmad Sufyan Zauri (Universitas PGRI Semarang, 2022)
The purpose of this study was to determine the level of student needs for worksheets based on the IDEA learning model (Issue, Discussion, Establish, and Apply). This research method uses quantitative research with a survey approach. The survey was conducted on 60 students of the mathematics education study program at the Islamic University of Malang who have implemented the IDEA learning model with the help of worksheets based on the IDEA learning model. The survey data collected in this study were the results of filling out a questionnaire about the need for worksheets based on the IDEA learning model and student opinions about the development of these worksheets. The results showed that the percentage of scores from the results of filling out the questionnaire on the development of worksheets based on the IDEA learning model was 70.93% which was in the high category. The results of filling out the questionnaire also showed that 76% of students agreed that the student worksheets based on the IDEA learning model were developed. Data in the form of respondents' opinions show that 28% of respondents said student worksheets were very helpful in increasing understanding of the material and 20% of respondents said it made it easier for students to learn the material. Therefore, it is necessary to develop student worksheets based on the IDEA learning model.